Exploring The Link Between Learning And Firm Performance: An Empirical Study Of Private Manufacturing Firms In Yangon – Myanmar - Tuan, Nham Phong; Lwin, Khine Tin Zar (Asian Academy of Management (AAM), 2013)
This paper focuses on evaluating the performance of firms from the knowledge and learning perspective. The survey covered a random sample of 120 private manufacturing firms in industrial zones in the Yangon area. Two broad categories of learning are determined: Internal and external. Internal learning is captured by two domains of learning, individual and organisational, whereas external learning involves customers, competitors and suppliers. Firm performance is evaluated using two broad groups of aspects: Non-financial and financial. The ordinary least square (OLS) results show that first, different domains of learning affect firms’ performance differently. Individual, organisational and competitor learning impact firms’ non-financial performance, whereas other forms of learning do not. Second, the effect of different domains of learning on performance differs in accordance with the different aspects of performance measurement. Individual learning can explain firms' financial performance both directly and indirectly. However, organisational and competitor learning explain firm financial performance indirectly. Third, non-financial performance affects financial performance. Thus, the empirical results have important implications.